2015
DOI: 10.3748/wjg.v21.i15.4757
|View full text |Cite
|
Sign up to set email alerts
|

Hand-sewnvslinearly stapled esophagogastric anastomosis for esophageal cancer: A meta-analysis

Abstract: This meta-analysis indicates that the LS technique contributes to a reduced rate of leakage and stricture compared with the HS method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 30 publications
2
53
0
5
Order By: Relevance
“…Multiple reports have compared anastomotic leak rates among various techniques. A recent meta‐analysis found lower leak rates with a linear stapled esophagogastric anastomosis compared to a completely hand‐sewn technique . A separate meta‐analysis by the same authors found no difference in leak rates between linear stapled and circular stapled esophagogastric anastomoses, but there were significant different stricture rates .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Multiple reports have compared anastomotic leak rates among various techniques. A recent meta‐analysis found lower leak rates with a linear stapled esophagogastric anastomosis compared to a completely hand‐sewn technique . A separate meta‐analysis by the same authors found no difference in leak rates between linear stapled and circular stapled esophagogastric anastomoses, but there were significant different stricture rates .…”
Section: Discussionmentioning
confidence: 98%
“…Different esophagogastric anastomotic techniques have their own characteristics, and multiple reports have compared anastomotic complications among various techniques . A side‐to‐side anastomosis has been generally defined as a semi‐mechanical liner stapler procedure, and in several studies it has been shown to reduce the incidence of postoperative anastomotic strictures without increasing the rate of anastomotic fistulae . At present, there are relatively few studies using a mechanical anastomosis, especially as it is applied to cervical anastomoses during MIE procedures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por el contrario, en un metaanálisis de Deng, et al, se presentó una tasa menor de fugas en las anastomosis laterolaterales con sutura mecánica lineal en comparación con la sutura manual. La diferencia con nuestros resultados puede deberse a la falta de homogeneidad en la técnica utilizada, pues se in-cluyeron pacientes con diferentes tipos de anastomosis con sutura mecánica 28 . En la presente serie, no se encontró una diferencia significativa en las complicaciones al usar sutura mecánica circular o lineal, en forma similar a lo informado por Zhou, et al, en su metaanálisis sobre fugas de las anastomosis; ellos informaron también un aumento de las estenosis, un aspecto que no fue evaluado en este estudio 29 .…”
Section: Discussionunclassified
“…7,31 However, the hand-sewn method performed thoracoscopically cannot be compared to the robotic-assisted hand-sewn method. In a review by Deng et al, the stapled methods were shown to lead to a reduced leak rate; 32 however, this does not prove the superiority of this method.…”
Section: Intrathoracic Anastomosis In Ramiementioning
confidence: 99%